Regulation Mechanism of Exogenous Brassinolide on Bulbil Formation and Development in Pinellia ternata - Guo, Chenchen; Li, Jigang; Li, Minghui; Xu, Xihang; Chen, Ying; Chu, Jianzhou; Yao, Xiaoqin (Frontiers in Plant Science, 2022)
The bulbil is the propagative organ of the P. ternata, which has a great effect on the yield of P. ternata. It is well known that plant hormones play important roles in bulbil formation and development. However, there is not clear about brassinolide (BR) regulation on bulbil formation and development. In this study, we revealed the effects of BR and BR biosynthesis inhibitors (propiconazole, Pcz) application on the histological observation, starch and sucrose metabolism, photosynthesis pathway, and hormone signaling pathway of P. ternata. The results showed that BR treatment reduced starch catabolism to maltodextrin and maltose in bulbil by decreasing BAM and ISA genes expression and increased cellulose catabolism to D-glucose in bulbil by enhancing edg and BGL genes expression. BR treatment enhanced the photosynthetic pigment content and potential maximum photosynthetic capacity and improved the photoprotection ability of P. ternata by increasing the dissipation of excess light energy to heat, thus reduced the photodamage in the PSII center. BR treatment increased the GA and BR content in bulbil of P. ternata, and decreased the ABA content in bulbil of P. ternata. Pcz treatment increased the level of GA, SL, ABA, and IAA in bulbil of P. ternata. BR regulated the signal transduction of BR, IAA, and ABA to regulate the formation and development of bulbil in P. ternata. These results provide molecular insight into BR regulation on bulbil formation and development.